2011
DOI: 10.1017/jfm.2011.276
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of a jet from a blunt body opposing a supersonic flow

Abstract: Numerical investigation of a sonic jet from a blunt body opposing a supersonic flow with a free stream Mach number M ∞ = 2.5 was carried out using large-eddy simulation for two total pressure ratios of the jet to the free stream, i.e. P = 0.816 and 1.633. Results have been validated carefully against experimental data. Various fundamental mechanisms dictating the flow phenomena, including shock/jet interaction, shock/shear-layer interaction, turbulent shear-layer evolution and coherent structures, have been st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(24 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…The dissipative elements in their study were: (1) the CC-hyperviscosity for shock capturing, (2) explicit Smagorinsky model for turbulence closure, (3) upwind biased discretization of the convective terms, and (4) usage of tetrahedral mesh for the simulations. The observations 5,33 motivate further developments and application of FVM for compressible jet flows.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The dissipative elements in their study were: (1) the CC-hyperviscosity for shock capturing, (2) explicit Smagorinsky model for turbulence closure, (3) upwind biased discretization of the convective terms, and (4) usage of tetrahedral mesh for the simulations. The observations 5,33 motivate further developments and application of FVM for compressible jet flows.…”
Section: Introductionmentioning
confidence: 83%
“…As mentioned by Pirozzoli,31 further studies on supersonic flows with unstructured FVM-codes are required. Recently, FVM was used in LES of a blunt body opposing a supersonic jet by Chen et al 33 The dissipative elements in their simulations were: (1) central/upwind scheme for shock capturing and (2) explicit closure model for turbulence. LES of an impinging supersonic jet was carried out by Dauptain et al 5 using a third order accurate FVM code.…”
Section: Introductionmentioning
confidence: 99%
“…The deviatoric part of the SGS stresses are given by −u i u j d = ν t (∂u i /∂x j + ∂u j /∂x i ) where u i is the resolved field. DES97 or delayed detached eddy simulation (DDES) (Spalart et al 2006) are well adapted to simulate massively separated flows characterized by a large-scale unsteadiness dominating the time-averaged solution (Chen, Xu & Lu 2010;Chen, Wang & Lu 2011). Nevertheless, it has been recognized by these authors (Shur, Spalart & Strelets 2005;Spalart 2009;Deck 2012b) and observed by others (Kok & Van der Ven 2012;Uzun & Hussaini 2012) that DDES may present a delay in the formation of instabilities in thin shear layer flows which can have dramatic sequels on the pressure (and, thus, acoustic) field (Deck 2012a).…”
Section: Zdesmentioning
confidence: 99%
“…Among these modes, the most energetic ones may correspond to the dominant spatial structures, which can be used to obtain the low-dimensional approximate descriptions for the high-dimensional field. The POD method has been used to analyze various flow phenomena such as turbulent flow [5,6], jet [7][8][9], flow control for circular cylinder [10][11][12][13], engine flow [14][15][16], backward-facing step flow [17], flow around a vibrating cantilever plate [18] and high-speed train model [19]. These studies indicate that the POD is an effective method for identifying dominant features and events in both experimental and numerical data.…”
Section: Introductionmentioning
confidence: 99%